2018
DOI: 10.1097/njh.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Facilitators and Challenges of Translating a Lung Cancer Palliative Care Intervention Into Community-Based Settings

Abstract: Despite significant progress in implementing palliative care interventions for patients with cancer, few intervention studies seek health care clinicians' input before implementation of these into the community. The purpose of this study was to explore palliative care and oncology clinicians' perspectives on the perceived facilitators and challenges in meeting the quality-of-life needs of patients with lung cancer and family caregivers in community-based settings. The Reach Effectiveness Adoption Implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…This article focuses on the perceived factors that facilitate and challenge oncology and palliative care clinicians in their efforts to address patients' and family caregivers' spiritual needs. The overall qualitative study and methods have been reported elsewhere (Siler, Mamier, & Winslow, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This article focuses on the perceived factors that facilitate and challenge oncology and palliative care clinicians in their efforts to address patients' and family caregivers' spiritual needs. The overall qualitative study and methods have been reported elsewhere (Siler, Mamier, & Winslow, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Three studies reported that in directing the spiritual needs of the patient, thereby promoting spiritual wellness and maintaining hope. Interprofessional team support is needed like doctor, nurse, social worker and chaplain [16,17,18]. The inclusion of spiritual care in quality palliative care of oncology practice is a team approach .…”
Section: Subtheme 11: Interprofessional Team Supportmentioning
confidence: 99%
“…[16] "Chaplains are unofficially part of the group, but when we see patients and families, [the chaplain] really knows what questions to pinpoint to ask." [18]…”
Section: Subtheme 11: Interprofessional Team Supportmentioning
confidence: 99%
See 2 more Smart Citations